Psychoanalytic theory : an introduction - Elliott, Anthony, 1964- (2015)
"This comprehensive introduction to psychoanalytic theory and its application to the social sciences and humanities is now available in a new and fully revised edition. Elliott provides lucid interpretations of key psychoanalytic theorists and examines the political and cultural dimensions of psychoanalytic studies"--
Machine generated contents note: -- 1. The Making of the Self - Divergences in Psychoanalytic Theory -- 2. Modern Culture and Its Repressed - From Freud to Lasch -- 3. Object Relations, Kleinian Theory, Self-Psychology - From Erikson to Kohut -- 4. Poststructuralist Anxiety: Subjects of Desire - From Lacan to Derrida -- 5. Psychoanalytic Feminism - From Chodorow to Butler -- 6. The Dislocating World of Postmodernism - Identity in Troubled Times -- Conclusion: Psychoanalysis as Critical Theory.
Includes bibliographical references (pages 192-197) and index.
Keywords: Psychoanalysis; PSYCHOLOGY / General; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Movements / Psychoanalysis; SOCIAL SCIENCE / Social Work; SOCIAL SCIENCE / Sociology / General